Subverting neoliberalism through a design framework for transformative game - French, Leia (My University, 2022)
Neoliberalism is the dominant order of our time. It has contributed to an age of escalating economic deregulation, privatisation, inequality, poverty and employment precarity – shifting the responsibility of governments to individuals while promoting a mindset of competitiveness, consumerism and individualism. Video games, as cultural artefacts, often reflect aspects of dominant neoliberal culture. Primed to immerse and persuade, video games can capture the attention of millions of players – and in positively mirroring neoliberal ideology, they can serve to unwittingly naturalise it. It is argued that if games can entice consent to the dominant order, it is possible that they can inspire resistance to it. However, studies show that persuasive games which engage with critical social issues in an explicit, literal manner are less likely to cause a change of heart than games that take a more indirect approach. This paper proposes a design framework for transformative games as a way of making more engaging, transformational games that can inspire critical reflection and player transformation without sacrificing player enjoyment. To demonstrate and assess the potential of this design framework, it was embedded in a purposefully created transformational game, Double-Edged Chord, aimed at subverting neoliberalism. This report details how an artsbased, transformative, mixed-method approach was used to develop and assess the potential of the design framework and its medium, the game. An analysis of pre-game questionnaires and guided post-game diary responses of 53 play-testers suggest that the framework and game hold transformative potential: Participant responses indicate that Double-Edged Chord resonated with the majority of players and demonstrated relative success in transforming awareness, knowledge and attitudes about neoliberal practices – helping players to re-imagine a world founded upon more humane values of equality, justice, empathy and cooperation. In this light, this study hopes to render visible and subvert neoliberalism’s impact both in-game and in reality.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Arts to the Faculty of Humanities, School of Arts, University of the Witwatersrand, Johannesburg, 2022